Extensão e sustentabilidade social no Instituto Federal da Paraíba/Campus João Pessoa - Monteiro, Gizelda Lyra (2022)
The present work aimed to research extension and social sustainability at the Federal Institute of Education, Science and Technology (IFPB) and answer the following question: in the scope of the Extension, what conception of social sustainability predominated in the IFPB/Campus João Pessoa and how extensionist actions promoted sustainability in the social sphere? For this, the indicators of the extension actions developed by the IFPB/João Pessoa campus referring to Projects, Nucleus and Enterprises, between 2014 and part of 2021, and the relationship with the theoretical discussion about the Sustainability category and its social dimension, from the contributions of authors such as John Elkington (1994) and Ignacy Sachs (2004), as well as academic works and documents that address the theme. In methodological terms, the research can be classified as qualitative, supported by quantitative data, bibliographical, documental and structuralist. As part of the analysis, the information regarding the Thematic Areas of the Projects, Nuclei and Extension Ventures of the João Pessoa campus, available in the Indicator Reports, was considered. About research findings, that made it possible to verify which thematic areas are classified according to the concept of social sustainability and the quantitative number of extension actions according to each area, based on the theoretical discussion presented and the data analysis, it is possible to think, together with the institution and society, of ways to expand actions in areas with a lower concentration of activities related to social sustainability, given the importance for the process of building a more just society; encourage greater participation of technical-administrative public employee, adding different types of perspectives and knowledge to the actions; encourage communities to be multipliers of knowledge and new actions, and, finally, open spaces for debate and development of other studies that contribute to the strengthening of the IFPB Extension and, consequently, of society.